Recent Progress in Hydrogen-Bonded π-Conjugated Systems Displaying J-Type Aggregates - Ávila-Rovelo, Nelson Ricardo; Ruiz-Carretero, Amparo (Organic Materials, 2020)
Supramolecular approaches are of great interest in the design of functional materials. The types of aggregates arising from different noncovalent interactions endow materials with intriguing properties. In this sense, J-type aggregates are very attractive due to their unique optical properties and capacity to transport excitons. These features make them great candidates in the design of materials for organic electronic devices. Furthermore, the incorporation of additional hydrogen-bonding functionalities provides J-aggregates with superior directionality and connection among the different π-conjugated cores. The control over the formation of H-bonds to achieve functional aggregates is therefore a promising strategy towards controlled structures with specific functions.This review outlines the most relevant and recent works of π-conjugated systems exhibiting J-type aggregates resulting from hydrogen-bonding interactions. Different types of hydrogen-bonding functionalities will be discussed together with their roles in the aggregate properties, their impact in the optoelectronic properties, the self-assembly mechanisms, and their applications in organic electronics.
Keywords: Hydrogen-bonding; J-aggregates; organic electronics